Canada's Distinguished Record of Sedimentary Geology - Miall, Andrew (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1998)
Summary The Leduc oil discovery in 1947 started a major research program in reef sedimentology that established Canadian science in the forefront, while in the area of clastic sedimentology, important developments in the study of bedforms and turbidity currents were made in the1960s. The growth of the petroleum industry helped to establish sedimentology as a major subdiscipline among professional geologists in Canada. The most significant scientific contributions in this country have been in the area of faciès studies and analysis of depositional environments. Developments in this area have formed much of the basis for the three editions of the highly successful GAC Fades Models book, that has soldnearly 70,000 copies since 1979. Canadian sedimentologists have also made significant contributions to the study of sequence stratigraphy, a field that is still growing. However, down-sizing of universities is bringing an era of achievement to an end, and future developments are likely to be in different areas of geology, particularly environmental studies.